PENGARUH SISTEM INFORMASI LOGISTIK DAN AKUNTABILITAS KINERJA TERHADAP FUNGSI LOGISTIK KORPS MARINIR - Teted Aries Gunawan; Christian L Tobing; Geger Jaka Kiswara (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The Navy Marine Corps (Kormar) is one of the TNI's Main Operational Commands (Kotama Ops) under the direct control of the TNI Commander. In the organizational structure of the TNI, which functions as Kotama Bin at the Navy Headquarters. In a war situation and the implementation of the tasks assigned to the Marine Corps, it is certain that continuous integrated logistics support (Integrated Logistic Support) is needed because success in a combat operation is largely determined by the smooth logistics support for operating units. The logistics function plays an important role for the Marine Corps (Kormar) in this case logistics functions to help smooth work and activities effectively and efficiently. One of the factors that affect Kormar's logistics function is the logistics information system. The decision-making process will not run well without the availability of information. Without comprehensive information it is difficult to make good decisions and if you are negligent in providing information accurately, effectively, and efficiently, it will hinder operational activities which in turn will prevent the organization from achieving the desired goals. Performance accountability of government agencies is one form of media to report the success or failure of a government agency on the implementation of organizational goals and objectives. The purpose of this study was to see how much influence the logistics information system and performance accountability had on the logistics function of the Marine Corps. The method used in this research is quantitative by processing the data from the questionnaire using the SPSS 25 application program. The sample used in this study is a member of the Marine Corps, totaling 76 people. The results in this study indicate that there is a positive and significant effect between the logistical information system variables on the logistics function of the Marine Corps. The t-test value is 3.731 and the t-table is 1.666. there is a positive and significant effect between the performance accountability variables on the logistics function of the Marine Corps. The t-test value is 7.607 and the t-table is 1.666. there is a positive and significant effect between the variables of logistics information systems and work accountability on the logistics function of the Marine Corps. The f test value is 34,734 and f table is 3,124. The value of the coefficient of determination or R2 48.8% Logistics Function can be explained by the Logistics Information System variable while the remaining 51.2% is influenced by other variables outside the model studied